Studi Sosiolinguistik Tentang Campur Kode Bahasa Inggris-Indonesia dalam Berbicara Di SMP Islam Al-Azhar Makassar - Suryani Jihad (Universitas Negeri Makassar, 2017)
This research aims to find out what forms of code mixing are used in speaking. The research employed a descriptive method. The subject of this research was the seventh grade of SMP Islam Al-Azhar in academic year 2014/2015. This research used cluster sampling. The sample of this research consisted of 20 students from 60 students as the total of population. This research used two instruments: notes and questionnaire. Notes from the spies were used to find out the forms of code mixing, observation was used to identify the forms of code mixing. The result of the research shows that there were three forms of code mixing that occurred namely: intra-sentential code mixing, intra-lexical code mixing and involving a change of pronunciation. The intra-sentential code mixing was the most frequently mixed points in English-Indonesian code mixing.